Current status and future perspectives in laparoendoscopic single-site and natural orifice transluminal endoscopic urological surgery. - Autorino, R (2013)
Objective of this study is to provide an evidence-based analysis of the current status and future perspectives of scarless urological surgery. A PubMed search has been performed for all relevant urological literature regarding natural orifice transluminal endoscopic surgery (NOTES) and laparoendoscopic single-site surgery (LESS). In addition, experience with LESS and NOTES at our own institution has been considered. All clinical and investigative reports for LESS and NOTES procedures in the urological literature have been considered. A wide variety of clinical procedures in urology have been successfully completed by using LESS techniques. Thus far, experience with NOTES has largely been investigational, although early clinical reports are emerging. Further development of instrumentation and platforms is necessary for both techniques to become more widely adopted throughout the urological community.